KEVALIDAN MODUL AJAR MATEMATIKA KURIKULUM MERDEKA MATERI RASIO KELAS VI SEKOLAH DASAR BERBASIS PROBLEM-BASED LEARNING: MODUL AJAR RASIO - Retni Abdilla; Syafri Ahmad; Salmaini Salmaini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to develop and validate a teaching module for Mathematics in grade VI elementary school on ratio material using the Merdeka Curriculum with Problem-Based Learning (PBL) approach. The research employed a development model involving expert validation on content, language, and media aspects. Data analysis used Likert scale instruments, showing post-revision validity scores of 90.10% (content), 87% (language), and 91.6% (media), all categorized as highly valid. The module supports meaningful learning, contextual examples, and differentiated assessments, enhancing students' proportional reasoning and numeracy skills for real-life applications